Characterization of Terahertz Emission from High Resistivity Fe-doped Bulk Ga0.69In0.31As Based Photoconducting Antennas - Sengupta, Suranjana (Springer Theses, Recognizing Outstanding Ph.D. Research, 2011)
Terahertz science and technology is attracting great interest due to its application in a wide array of fields made possible by the development of new and improved terahertz radiation sources and detectors. This book focuses on the development and characterization of one such source - namely the semi-large aperture photoconducting (PC) antenna fabricated on Fe-doped bulk Ga0.69In0.31As substrate. The high ultrafast carrier mobility, high resistivity, and subpicosecond carrier lifetime along with low bandgap make Ga0.69In0.31As an excellent candidate for PC antenna based THz emitter that can be photoexcited by compact Yb-based multiwatt laser systems for high power THz emission. The research is aimed at evaluating the impact of physical properties of a semi-large aperture Ga0.69In0.31As PC antenna upon its THz generation efficiency, and is motivated by the ultimate goal of developing a high-power terahertz radiation source for time-domain terahertz spectroscopy and imaging systems. This Doctoral Thesis has been accepted by Rensselaer Polytechnic Institute, Troy, USA.